2019
DOI: 10.7759/cureus.5295
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary Syndrome in a Thirteen Year Old Boy: A Case Report

Abstract: Hepatopulmonary syndrome (HPS) is a late complication associated with liver cirrhosis. Recent studies have suggested that it can also occur in non-cirrhotic portal hypertension. The criteria that need to be met for making the diagnosis of HPS include chronic liver disease, impaired gaseous exchange leading to hypoxemia and intrapulmonary vascular dilation. The pathophysiology of this disease includes mediators like nitric oxide (NO), and endothelial growth factors which play an important role in intrapulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Moderate alcohol intake could increase FEV 1 and FVC improve lung function (70) potentially by enhancing mucociliary clearance, stimulating bronchodilation, and even alleviating airway damage (59). In contrast, chronic alcohol exposure often leads to hepatopulmonary syndrome, which can cause respiratory impairment (71). In this study, univariate analysis revealed a statistically significant association between lung ventilation function and alcohol consumption, while multivariable analysis showed the opposite finding.…”
Section: Discussionmentioning
confidence: 49%
“…Moderate alcohol intake could increase FEV 1 and FVC improve lung function (70) potentially by enhancing mucociliary clearance, stimulating bronchodilation, and even alleviating airway damage (59). In contrast, chronic alcohol exposure often leads to hepatopulmonary syndrome, which can cause respiratory impairment (71). In this study, univariate analysis revealed a statistically significant association between lung ventilation function and alcohol consumption, while multivariable analysis showed the opposite finding.…”
Section: Discussionmentioning
confidence: 49%
“…Among the complications of chronic liver disease, HPS has a prevalence ranging from 4-47% depending on diagnostic criteria, methods used and population studied. On average the prevalence is 25% [1,2]. It presents with exertional dyspnoea, platypnoea, orthodeoxia, cyanosis and digital clubbing [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…On average the prevalence is 25% [1,2]. It presents with exertional dyspnoea, platypnoea, orthodeoxia, cyanosis and digital clubbing [1][2][3]. The pathogenesis of HPS has not been clearly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations